Analisis Faktor yang Berperan dalam Keputusan Konsumen Memilih Varietas Beras di Pasar Bauntung Kota Banjarbaru Kalimantan Selatan - Kiptiah Kiptiah; Djoko Santoso; Rifiana Rifiana (Universitas Lambung Mangkurat, 2015)
Banjarbaru is a city with themulti-ethnic population from various ethnic groups of Banjar, Java, and others. As a result, they have different consumption pattern and preference of rice. The study identifies the effect of the consumer's socio-economic characteristic in determining their choices on particular rice variety consumed. The study reveals that the internal factor in the family (the housewife) has a significant role in deciding the chosen rice. The particular rice is chosen mainly because of taste, while economic factors are not the decisive factor. This finding makes sense since rice is the staple food. The consumershave good perception on rice trader performance, but they dissatisfy vatn the taste, shape, and hygiene of traded rice in the local market.